Retrospective analysis of patients with Chronic Myeloid Leukaemia (CML) at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) Medical Oncology Unit (2002-2015) - Tshabalala, Dineo (My University, 2017)
Background: The objective of this study is to explore the use of bcr-abl Tyrosine Kinase Inhibitors in the treatment of chronic myeloid leukemia (CML) patients at the CMJAH Medical Oncology Unit in Johannesburg, South Africa, and to confirm the evidence from bodies such as the European LeukaemiaNet (ELN) that the era of bcrabl TKIs has significantly advanced the treatment of CML, with affected patients living normal lives in their chronic phase, therefore making allogeneic stem cell transplantation no longer an essential part of therapy. Method: A cohort of 101 adult patients diagnosed with CML, 48% males and 52% females, with a median age of 40 years, were retrospectively analysed using data from their clinic files. The Sokal score could be evaluated as a pretreatment prognostic tool in 55% of the patients. Molecular responses to three sequential TKIs ie. Imatinib followed by dasatinib and nilotinib, were sought by the monitoring of serial RQ-PCRs. Adverse effects and mutational analyses were also analysed. Results: Once patients were started on bcr-abl TKI therapy (post the interferon-α era), better treatment responses were seen and better overall survival achieved without progression to advanced stages of CML. In addition, second line TKI therapy showed a benefit following the first line TKI imatinib. TKIs were generally well tolerated with 63 of the 101 patients experiencing grade 3/ 4 AEs mainly due to haematological toxicity. A low number of documented mutations (3 out of 101) also suggest that TKI therapy is very effective in treating CML. Conclusion: There seems to be an improved outcome with TKI therapy compared to the older interferon alpha based therapy; as well as a treatment response with second generation TKI therapy in patients at the CMJAH Medical Oncology unit treated for CML. Patients on TKI therapy remained in CP-1 of CML for longer periods without transformation to advanced stages of CML, with improved PFS and 5 year OS, as long as they were compliant on treatment. Hematological adverse effects were observed due to both dasatinib and imatinib therapy. Key words: Chronic myeloid leukaemia; Tyrosine kinase inhibitor; Molecular response; Overall survival; Progression free survival.
A dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand in fulfillment of the part requirements of the Degree of Master of Medicine in Internal Medicine Johannesburg 2017.
Keywords: Leukemia, Myelogenous, Chronic, BCR-ABL Positive